Reliability analysis of dynamic systems efficient probabilistic methods and aerospace applications - Wu, Bin (Elsevier and Shanghai Jiao Tong University Press aerospace series)
This book presents the latest probabilistic techniques for accurate and efficient dynamic system reliability analysis. In particular, it focuses on large aerospace systems under harmonic loads in the low frequency range.